2022
DOI: 10.3389/fneur.2022.917967
|View full text |Cite
|
Sign up to set email alerts
|

The elephant in the room: Intimate partner violence, women, and traumatic brain injury in sub-Saharan Africa

Abstract: BackgroundIntimate partner violence (IPV) is a gendered form of violence that has been linked with traumatic brain injury (TBI). The prevalence of IPV in sub-Saharan Africa (SSA) is estimated to be one of the highest globally. Yet, little is known about the association between IPV and TBI in the SSA context. In this scoping review, we examine the intersection between IPV and TBI in SSA to identify gaps, as well as intervention opportunities.MethodsUsing the Preferred Reporting Items for Systematic Reviews and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The citations for the studies included in this analysis can be found in the Reference section [34,36,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The citations for the studies included in this analysis can be found in the Reference section [34,36,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…People living in remote areas have an increased risk of neurotrauma following an accident [62]. Women are at a greater risk of TBI due to domestic violence [54,62].…”
Section: Data Availability Statementmentioning
confidence: 99%